Analisis dan Perancangan Aplikasi Mobile untuk Donasi menggunakan Metode Hybrid berbasis React Native - Muhammad Abdul Karim; Ahmad Rio Adriansyah (LPPM STT Terpadu Nurul Fikri, 2022)
This study discusses the design of mobile-based goods donation applications using the framework React Native. In Indonesia, there are many online donation platforms, but most donations are money. However, the first needs of victims of natural disasters are not money but primary goods. In addition, based on Carousell's Preloved Indonesia 2017 Trends Report, 82% of the 1,000 respondents piled up unused items in their homes in Indonesia. Therefore, a mobile-based item donation application makes, where donated goods are items that have not been used. The goal is to make it easier for users to donate goods, wherever and whenever. The application builds using the framework React Native with RESTFul API and MySQL as a database programming language. Tests carried out are functional system testing using black-box testing and User Acceptance Test (UAT) and testing using a questionnaire. The functional system runs according to the defined requirements based on the test results. The test results are based on 100% black-box testing and 100% UAT and questionnaires with an average value of 87.4%.